Exploring Self-Efficacy Faced by Pre-Service English Teachers in Teaching Practicum: A Case Study on Kampus Mengajar Program - Dwijayanti, Julia; Fatoni, Mohammad; Wardhono, Agus; Tauchid, Ahmad (New Language Dimensions, 2024)
A pre-service English teacher's self-efficacy is under explore in Kampus Mengajar Program. Self-efficacy refers to people's perceptions of their ability to perform at specified levels and influence aspects of their lives. This study employs qualitative research. In this study, researchers collected data through questionnaires and interviews. The study reveals that pre-service English teachers at Kampus Mengajar have high self-efficacy.  The research expanded to investigate how strong self- efficacy and the factors regarding this phenomenon. The three components identified are personal factors, behavioral factors, and environmental factors that carry out all of their success in the Kampus Mengajar program optimally. This study gives benefits for Preservice English teachers in understanding the self-efficacy to carry out Kampus Mengajar Program were explored. Suggestions for further research are to use mixed methods and add male participants to direct new research trends in gender and self-efficacy.